ADVANCEMENTS IN SURGICAL TECHNIQUES: A COMPREHENSIVE REVIEW - Kholmamatova Shahzoda; Imran Aslam; Ayesha Ashraf; Abdurakhmanova Zamira Ergashboevna; Eshkobilova Mavjuda Ergashboevna (TADQIQOTLAR, 2025)
Abstract: Surgery has been an essential component of medical practice for many years, continuously improving patient outcomes and reducing morbidity and death. This research article provides an overview of recent advancements in surgical techniques from a range of disciplines. It examines developments in minimally invasive surgery, tissue engineering, artificial intelligence (AI), robotic surgery, and augmented reality (AR). It also discusses the challenges that the surgical profession will face in the future, including the importance of surgeon education and training and the ethical implications of new technological developments.